(untitled) (Eureka Journal of Humanities and Social Research, 2026)
The article discusses the development of physical abilities, the development of qualitative training, the achievement of positive results, the strengthening of qualities through repeated exercises, and the need to impose a certain requirement on football players: the ability to use physical qualities as a means of increasing game efficiency.